Emerging pests of millets and their management - Prasad, G Shyam; Stanley, J; Babu, KS; Kalisekar, A; Padmaja, P G; Subbarayudu, B (Indian Farming, 2023)
There are about 150 insect pests reported in millets out of which shoot flies, stem borers and earhead midges are considered as major pests. In India, yield losses of 10–20% have been reported in millets due to insect pests. Shoot flies and stem borers are associated with millets and cause huge damage apart from many sucking pests. Few pests are newly observed attacking millets and few minor pests have become major in some regions. For most of the recently recorded pests, information on factors responsible for their outbreak, bionomics, yield losses etc is needed before planning their control operations. As an immediate remedy, chemicals have been used mainly on high yielding varieties and hybrids. However, a combination of cultural practices and resistant cultivars has proved to be effective.